Intracellular Major Histocompatibility Complex Class II and C-X-C Motif Chemokine Ligand 10-Expressing Neutrophils Indicate the State of Anti-Tumor Activity Induced by Bacillus Calmette–Guérin - Yuji Takeda; Tomoyuki Kato; Saima Sabrina; Sei Naito; Hiromi Ito; Naoto Emi; Yuya Kuboki; Yuki Takai; Hiroki Fukuhara; Masaki Ushijima; Takafumi Narisawa; Mayu Yagi; et al. (Biomedicines, 2023)
(1) Background: Inflammatory responses induce the formation of both anti-tumor and pro-tumor neutrophils known as myeloid-derived suppressor cells (MDSCs). Intermittent intravesical infusion of Bacillus Calmette–Guérin (BCG) is an established cancer immunotherapy for non-muscle-invasive bladder cancer (NMIBC). However, the types of neutrophils induced via the inflammatory response to both tumor-bearing and BCG remain unclear. (2) Methods: We therefore analyzed neutrophil dynamics in the peripheral blood and urine of patients with NMIBC who received BCG therapy. Further, we analyzed the effects of BCG in a mouse intraperitoneal tumor model. (3) Results: BCG therapy induced the formation of CXCL10 and MHC class II-positive neutrophils in the urine of patients with NMIBC but did not induce MDSC formation. CXCL10- and MHC class II-expressing neutrophils were detected in peritoneal exudate cells formed after BCG administration. Partial neutrophil depletion using an anti-Ly6G antibody suppressed the upregulation of CXCL10 and MHC class II in neutrophils and reversed the anti-tumor activity of BCG in mouse models. (4) Conclusions: These results indicated that intracellular MHC class II- and CXCL10-expressing neutrophils indicate the state of anti-tumor activity induced via BCG. The status of neutrophils in mixed inflammation of immunosuppressive and anti-tumor responses may therefore be useful for evaluating immunological systemic conditions.